Skala C.O.R.E. sebagai Alternatif Mengukur Kreativitas: Suatu Pendekatan Kepribadian - Suharnan (ANIMA Indonesian Psychological Journal, 2002)
The goal of the present research was to construct a psychological measurement of creativity through a personality approach. This tool is aimed to identify creative potentials referring to creative spirit, a willingness to act toward or producing new beneficial ideas. According to Ayan (1997), the creative spirit encompasses four main components of the personality characteristics: curiousity, openness to experiences, tolerance towards risks, and energy. These four characteristics of personality are revealed through a number of items or statements in Likert scale. So the C.O.R.E. scale is based on these theoretical aspects (curiousity, openness, risks, and energy). Subjects were high school and university students (N = 332; males and females), coming from urban as well as suburbans. The data were analysed with the factor analyses. Results reveal that this scale could identify four personality characteristics conforming to the theory. This scale has a high reliability coefficient and positively correlated to an existing creativity test, hence this scale should be a valid tool to measure creativity.